Russian-Western Relations in Light of the Repercussions of the Russian-Ukrainian Crisis 2014-2022 - Al-Arqan, Abdulla Rashed Salameh; Al-Omary, Manthour Saleh Mahmoud; Al Arqan, Sadam Abdulla (Dirasat: Human and Social Sciences, 2024)
Objectives: This study aims to investigate the impact of the Russian-Ukrainian crisis on Russian-Western relations from 2014 to 2022 and explore the future prospects for these relations during the crisis repercussions. Methods: The study adopts a combination of the decision-making, systems analysis, and analytical descriptive approaches to analyze the reflections of the Russian-Ukrainian crisis on Russian-Western relations. It draws from previous studies and research on the same topic, as well as monitoring media and published materials regarding the crisis. Results: The study reveals that the Russian-Ukrainian crisis stems from the competition between the US-led Western coalition and the Russian alliance, which fears NATO's eastward expansion posing a threat to its sovereignty. Simultaneously, the West considers Ukraine as crucial to accessing Russian strategic depth and undermining Russia's aspirations to be a major global player. The West utilized severe economic sanctions and supplied advanced weapons to Ukraine, contributing to the resilience of their army. The future vision for the conflict includes various scenarios, with resolution depending on the parties' willingness to negotiate for a peaceful solution or escalation leading to a devastating global war. Conclusion: The study concludes that the Russian-Ukrainian crisis has had a detrimental impact on Russian-Western relations, with both sides exploiting the situation to pursue their interests. The crisis is complex and significant, akin to one of the most critical post-Cold War crises, exposing conflicts, diverse policies, and the competition and contradictions between Western and Russian approaches.